Conjugated polymer-based composites for electrochromic applications - Che, Boyang (2019)
Electrochromism is a phenomenon that materials are able to change its color reversibly under external potential. The mechanism of electrochromic materials is redox reactions in most of the cases. Composite materials have been widely used for electrochromic applications, as they have the potential to exhibit the advantages of both components. Conjugated polymer-based composite is a popular option due to the conductivity and flexibility of conjugated polymers. The challenge in design of a high-performance composite material is to achieve synergistic effects in desired aspects instead of getting average performance of the components. The design guidelines of electrochromic composite are not well established. Thus, the aim of the thesis is to design new conjugated polymer-based composite systems in which the conjugated polymers and the other components are complementary in certain aspects, and study how interfacial interactions affect synergistic effects of the complementary components in conjugated polymer-based electrochromic composites. The key hypothesis is that with proper structural design, strong interfacial interactions between conjugated polymers and the other components may induce significant synergistic effects, positively influencing electron transport, oxidation/reduction potentials, electrochemical stability, and/or mechanical robustness. To verify the hypothesis, two composite systems have been studied are molybdenum trioxide/poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (MoO3/PEDOT:PSS) and polyaniline-carbon nanotube (PANI-CNT). The components have complementary properties in conductivities or mechanical properties. The interfacial interactions in each composite are electrostatic interaction and covalent bond, respectively. Both composites show enhanced electrochromic and electrochemical properties. It is proved that strong interfacial interactions between these two pairs of components induce significant synergistic effects. This conclusion provides a rationale for designing high-performance composite materials for electrochromic applications.